Exploring Sustainable Practices Adoption Among Micro, Small, And Medium Enterprises - Muhammad Arif Rahman,; Merry Christina,; Dipa Rizky Wijaya, (Jurnal Publikasi Ilmu Manajemen, 2022)
This study investigates the adoption of sustainable practices among Micro, Small, and Medium Enterprises (MSMEs). The research aims to understand the factors influencing the uptake of sustainable practices in MSMEs, exploring the complexities of implementation within this sector. Employing a qualitative research design, data were gathered through semi-structured interviews and thematic analysis. A purposive sampling technique was utilized to select participants representing diverse MSMEs. The findings reveal multifaceted insights into the motivations, challenges, and strategies associated with sustainable practices adoption among MSMEs. The study contributes to a deeper understanding of how MSMEs engage with sustainability initiatives and offers implications for policy, practice, and future research endeavors.